Analisis Perhitungan dan Perlakuan Akuntansi Bagi Hasil atas Surplus Underwriting Dana Tabarru’ - Ereda Widianingsih; Hasanudin Hasanudin (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2023)
Sharia economic activity in Indonesia is growing, including sharia insurance, which tends to increase although not very encouraging because the number is still around 1% of the total population of Indonesia. This is due to the lack of socialization about the importance of sharia insurance, including about tabbarru' and the distribution of the results for the underwriting surplus. The study was conducted to determine the treatment and calculation of profit sharing for the excess funds. The research method will emphasize whether or not the treatment has followed PSAK 108. Based on the analysis, it can be concluded that this sharia insurance company in applying the profit-sharing accounting treatment is in accordance with the rules in PSAK number 108, namely sharia accounting standards. Thus, hopefully it can become a reference for the community so that they do not hesitate in following this sharia insurance.